Rationale for the treatment of unilateral cleft lip - GC4 protocol - Anhad Mehra; Hiteswar Sarma (Wolters Kluwer Medknow Publications, 2021)
Introduction: The aim of this study is to retrospectively analyze the surgical outcomes of 200 patients who were treated for unilateral cleft lip (UCL) over a period of 4 months in our cleft care center. Materials and Methods: This is a retrospective audit of all the patients who had undergone UCL repair from January to April 2019. The patients were stratified based on the cleft severity. Fisher technique was employed for the correction of incomplete cleft lip while modified Mohler technique was the choice of repair for complete cleft lip. Clinical records including each patient's preoperative and postoperative photographs were taken into consideration. Results: Of the 200 patients who had undergone lip repair, 56% were male and 44% were female. The average age of the patients treated was 10.5 months. Visual Analog Scale (VAS) and Scar Assessment Scale were used to evaluate the scar, taking into account pigmentation, vascularity, acceptability, parent comfort, and contour. The results ranged from "excellent" and "good" in the case of incomplete cleft lip repair to "good" and "acceptable" in the case of complete cleft lip repair. Postoperative follow-up revealed that 5 of them had complications related to dehiscence and bleeding. Conclusion: Fisher's method in patients with unilateral incomplete cleft lip proved the effectiveness in improving the esthetic results with good symmetry while the Mohler modification of Millard technique helped achieve optimal lip length with acceptable esthetics.